Quality of life of urban poor in Shillong - Mohapatra, A.C.; Das, Susmita (1998)
With accelerating urbanisation in developing countries like India, not only the number and proportion of the urban poor is increasing, without adequate and effective public investment in urban infrastructure, the situation of the urban poor is getting precarious day by day. One of the main concerns of urban social planning is objective assessment of the quality of life of the poor. There are studies, invariably on large and mega-cities, where the problems of the poor are starkly visible. However, the situation in smaller and middle sized cities is no better. The present paper makes an attempt to study the quality of life of the poor in the north-eastern Indian city of Shillong. - Reproduced
Keywords: Quality of life - India - Meghalaya; Urban poor - India - Meghalaya; Poverty - India - Meghalaya; Poverty